2001
DOI: 10.1152/jn.2001.86.4.2001
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Task-Irrelevant Visual Features by Primate Prefrontal Neurons

Abstract: The primate brain is equipped with prefrontal circuits for interpreting visual information, but how these circuits deal with competing stimulus-response (S-R) associations remains unknown. Here we show different types of responses to task-irrelevant visual features in three functionally dissociated groups of primate prefrontal neurons. Two Japanese macaques participated in a go/no-go task in which they had to discriminate either the color or the motion direction of a visual target to make a correct manual resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
5
36
2
Order By: Relevance
“…This idea is consistent with data showing task-dependent changes in background or undriven activity in high-order cortical areas (Sakagami & Niki, 1994;Lauwereyns et al, 2001;Port, Kruse, Lee, & Georgopoulas, 2001). Although it is not surprising that widespread excitation can produce drastic changes in a network, the generality of this effect is not intuitively obvious.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This idea is consistent with data showing task-dependent changes in background or undriven activity in high-order cortical areas (Sakagami & Niki, 1994;Lauwereyns et al, 2001;Port, Kruse, Lee, & Georgopoulas, 2001). Although it is not surprising that widespread excitation can produce drastic changes in a network, the generality of this effect is not intuitively obvious.…”
Section: Discussionsupporting
confidence: 90%
“…When we need to remember a phone number announced on the radio, some neural process in the brain enables our short-term memory; without the context information indicating that it is important to store it, the same number vanishes promptly from the mind. In the motor realm, this is a classic problem that neurophysiologists have studied using go versus no-go paradigms (see, e.g., Schultz & Romo, 1992;Lauwereyns et al, 2001;Sommer & Wurtz, 2001). In these tasks, a subject performs one of several possible motor actions in response to a presented stimulus, but the movement is contingent on a separate cue giving either a go or a no-go instruction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a neuron active in conjunction with planning rightward saccades will begin to fire not only in response to a target flashed in the right visual field but also in response to a foveal digitized image instructing the monkey to make a rightward saccade (Olson et al 2000). Similar effects of training were observed in other oculomotor areas (Bichot et al 1996;Grunewald et al 1999;Horwitz et al 2004a;Lauwereyns et al 2001;Toth and Assad 2002). The present study, however, is the first to have shown that training monkeys to attend to locations as defined with respect to a particular reference frame induces neurons to represent locations relative to that frame.…”
Section: Discussionsupporting
confidence: 72%
“…Various neurophysiological studies have explored changes in neuronal properties as functions of multiple sensory cues in the spirit of the task proposed here (White and Wise, 1999;Lauwereyns et al, 2001;Wallis and Miller, 2003). Some of those results are consistent with context-dependent variations in gain but, because the paradigms were not designed to assess this, confounding factors are inevitable.…”
Section: Experimental Predictionsmentioning
confidence: 67%